Arctic climate change discourse: the contrasting politics of research agendas in the West and Russia - Forbes, Bruce C.; Stammler, Florian (2009)
In this paper we explore how Western scientific concepts and attitudes towards indigenous knowledge, as they pertain to resource management and climate change, differ from the prevailing view in modern Russia. Western indigenous leaders representing the Inuit and Saami peoples are actively engaged in the academic and political discourse surrounding climate change, whereas their Russian colleagues tend to focus more on legislation and self-determination, as a post-Soviet legacy. We contribute to the debate with data from the Nenets tundra, showing how different research has employed the three crucial Western research paradigms of climate change, wildlife management and indigenous knowledge on the ground. We suggest that the daily practice of tundra nomadism involves permanent processes of negotiating one’s position in a changing environment, which is why “adaptation” is woven into the society, and cosmology as a whole, rather than being separable into distinct “bodies” of knowledge or Western-designed categories. We argue that research agendas should be placed in their proper local and regional context, and temporal framework: for example, by collaborating with herders on the topics of weather instead of climate change, herding skills instead of wildlife management, and ways of engaging with the tundra instead of traditional ecological knowledge.